New challenges to infectious safety in the implementation of medical activities related to organ and tissue donation for transplantation - B. I. Yaremin; P. Kh. Nazarov; K. F.O. Alekberov; D. Yu. Konstantinov; E. V. Kudinova; U. V. Maslikova; M. S. Novruzbekov (Трансплантология (Москва), 2020)
Changes in current scientific literature and regulatory documents related to the issues of infectious safety in organ and tissue donation have been analyzed. The suggestions have been given for changing the existing practices to meet new challenges. Data on threats to the safety of organ and tissue donation associated with the COVID-19 pandemic have been presented.